A high temperature hydrophobic aerogel composite material and preparation method thereof
By introducing high-temperature resistant aerogels and functional additive components into the aerogel composite, the stability and insulation performance of the material in high-temperature and humid and heat environments are solved, and significant improvements in high-temperature and hydrophobic performance are achieved.
Patent Information
- Application Number
- CN202411278902.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Aerogel composites are prone to adsorbing water vapor in humid environments, resulting in increased thermal conductivity and reduced thermal insulation performance. At the same time, they are poor in stability in high-temperature environments and are easily affected by oxidation.
A high-temperature hydrophobic aerogel composite material is used, which includes epoxy resin, diluent, curing agent, anti-ultraviolet additive, flame retardant additive, high-temperature resistant aerogel, composite additive and functional additive components. Through a specific preparation method, it includes hydrolyzing ethyl orthosilicate under acidic conditions, adding mullite fibers and gelling, aging and drying under alkaline conditions to form a high-temperature resistant aerogel, and preparing composite additives by grafting caffeic acid to the surface of vermiculite to enhance antioxidant properties.
It significantly improves the high temperature resistance and thermal insulation properties of aerogel composites, extends the service life, and avoids the influence of oxidation in humid and heat environments, ensuring the stability and low thermal conductivity of the material.
Smart Images

Figure CN118909402B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a high-temperature hydrophobic aerogel composite material and a preparation method thereof. Background Art
[0002] With the continuous development of science and technology, the application of aerogel composites is increasing. Aerogel composites are a new type of material that has the characteristics of aerogels and the advantages of other materials. Aerogel composites are divided into inorganic aerogels, organic aerogels and organic-inorganic aerogels. It is a lightweight material with a nanoporous network structure and the network pores are filled with gaseous dispersion medium. It has many advantages such as ultra-low density, high specific surface area, high porosity, low refractive index, sound insulation, etc. The high specific surface area and high porosity make aerogel composites have extremely low thermal conductivity, and have great application potential in the field of thermal insulation.
[0003] Epoxy resin has excellent processing performance and dielectric properties, and is widely used in insulation, electronic and electrical industries. Aerogel itself is an excellent thermal insulation material. Adding aerogel to epoxy resin to prepare aerogel composites can improve the thermal insulation performance of the epoxy resin matrix. However, due to the porous structure of aerogel composites, it is easy to adsorb water vapor in a humid environment, resulting in increased thermal conductivity and decreased thermal insulation performance. At the same time, in order to make the aerogel composites maintain stable performance in high temperature environments and inhibit or slow down the effects of oxidation in humid and hot environments, the aerogel composites need to be modified so that the aerogel composites have low thermal conductivity, excellent high temperature resistance, hydrophobicity, antioxidant properties and mechanical properties to meet the thermal insulation needs in various environments.
[0004] Patent publication number CN113512272B discloses a method for preparing a low-thermal-conductivity aerogel-type epoxy resin thermal insulation composite material. The composite material is prepared by mixing aerogel particles with epoxy resin, then using negative pressure to remove bubbles, and centrifuging the mixture at different gradient speeds to improve the curing strength of the composite material. The prepared aerogel-type epoxy resin thermal insulation composite material has a low thermal conductivity coefficient and improved thermal insulation performance. However, the patent does not take into account the effects of oxidation on the aerogel composite material in a hot and humid environment and the application of hydrophobic aerogel composite materials. Therefore, the present invention provides a high-temperature hydrophobic aerogel composite material with a long service life and broad application prospects. Summary of the Invention
[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a high-temperature hydrophobic aerogel composite material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high-temperature hydrophobic aerogel composite material comprises the following raw materials in parts by weight: 70-90 parts of epoxy resin, 40-60 parts of diluent, 10-15 parts of curing agent, 1-3 parts of anti-ultraviolet additive, 1-3 parts of flame retardant additive, 5-8 parts of high-temperature resistant aerogel, 3-6 parts of composite additive, and 4-6 parts of functional additive components.
[0008] Furthermore, the method for preparing the high temperature resistant aerogel comprises the following steps:
[0009] S1. Deionized water and ethanol were added to ethyl orthosilicate, and the mixture was stirred and evenly mixed. Then, hydrochloric acid was added to adjust the pH to 3-4, and the mixture was hydrolyzed for 4-6 hours to obtain an aerogel hydrolyzate.
[0010] S2. Mullite fiber is added to the aerogel hydrolyzate and evenly dispersed. Then, dilute ammonia water is added to adjust the pH to 6-8. After 1-2 hours, a gel is formed. The gel is placed in anhydrous ethanol at room temperature for aging for 12-18 hours. Finally, it is dried at 45-65°C to obtain a high-temperature resistant aerogel.
[0011] By adopting the above technical solution, ethyl orthosilicate can be hydrolyzed under acidic conditions to obtain an aerogel hydrolyzate. After adding mullite fibers with excellent chemical stability and high temperature resistance, it is gelled, aged, and dried under alkaline conditions to obtain a high-temperature resistant aerogel. The mullite fibers are overlapped into a network internally, so that the prepared high-temperature resistant aerogel has excellent mechanical strength, a stable internal structure, and is not easy to collapse. When added to an epoxy resin matrix, it can significantly improve the high-temperature resistance of the aerogel composite material.
[0012] Furthermore, in step S2, the mass percentage of the mullite fiber in the aerogel hydrolyzate is 6-8%.
[0013] Furthermore, the preparation method of the composite additive comprises the following steps:
[0014] Step A, adding activated vermiculite to a sodium hydroxide solution with a mass fraction of 6-8% and dispersing the mixture uniformly, adding an epoxy modifier, and then placing the mixture in a water bath and raising the temperature to 60-70° C., reacting for 3-5 hours, cooling, washing, filtering, and vacuum drying to obtain modified vermiculite;
[0015] Step B: adding modified vermiculite into dimethyl sulfoxide and dispersing it evenly, then adding caffeic acid and p-toluenesulfonic acid, and then raising the temperature to 85-95° C., reacting for 4-6 hours, centrifuging, washing, and vacuum drying to obtain a composite additive.
[0016] By adopting the above technical solution, after the vermiculite is treated with hydrochloric acid, the active silanol groups can be exposed. Under alkaline conditions, the silanol groups in the activated vermiculite can undergo a ring-opening reaction with the epoxy groups in the epoxy modifier to obtain modified vermiculite with active hydroxyl groups. Under the action of p-toluenesulfonic acid, the active hydroxyl groups in the modified vermiculite undergo an esterification reaction with the active carboxyl groups in the caffeic acid structure, thereby grafting caffeic acid with antioxidant effects on the vermiculite surface to obtain a composite additive.
[0017] Furthermore, in step A, the method for activating vermiculite is to mix the vermiculite with a hydrochloric acid solution with a mass fraction of 6-8%, stir it in a water bath at 70-80°C for 1-2h, wash it until it is neutral, and dry it at 50-60°C to obtain activated vermiculite.
[0018] Furthermore, in step A, the epoxy modifier is any one of 1,2-epoxydodecane, 1,2-epoxytetradecane, 1,2-epoxyhexadecane or 1,2-epoxyoctadecane.
[0019] Furthermore, the preparation method of the functional additive component is as follows:
[0020] Ⅰ. Add polyisoprene to toluene, stir evenly, introduce nitrogen protection, then add mercaptoethylamine and benzoin dimethyl ether, and react under ultraviolet light for 2-3 hours. After the reaction is completed, wash and vacuum dry to obtain modified polyisoprene;
[0021] II. Add modified polyisoprene to N,N-dimethylformamide, stir evenly, introduce nitrogen protection, then add 3-bromopropyl tert-butyl dimethylsilyl ether and an alkaline catalyst, raise the temperature to 60-80°C, react for 4-6 hours, cool to room temperature, wash, and vacuum dry to obtain a functional additive component.
[0022] By adopting the above technical solution, the alkenyl group in the polyisoprene structure can undergo a click reaction with the active thiol group in the mercaptoethylamine structure under the irradiation of benzoin dimethyl ether and ultraviolet light, thereby introducing an active amino group into the polyisoprene to obtain a modified polyisoprene. The active amino group in the modified polyisoprene structure can undergo a substitution reaction with the active bromine substituent in the 3-bromopropyl tert-butyl dimethylsilyl ether structure under the action of an alkaline catalyst to obtain a functional additive component.
[0023] Furthermore, in step II, the alkaline catalyst is triethylamine or pyridine.
[0024] Furthermore, the diluent is acetone or xylene; the curing agent is methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride; the anti-ultraviolet additive is UV-1577 or UV-327; and the flame retardant additive is dimethyl methyl phosphate or toluene diphenyl phosphate.
[0025] A method for preparing a high-temperature hydrophobic aerogel composite material comprises the following steps:
[0026] Step 1: Add epoxy resin, diluent, anti-ultraviolet additive, flame retardant additive, high temperature resistant aerogel, composite additive, and functional additive component into a mixing tank and mix evenly. Centrifuge the mixture at 1000-2000 r / min for 3-5 minutes to obtain a mixture.
[0027] Step 2: Add the curing agent to the mixture, stir evenly, place in a vacuum drying oven and evacuate for 20-40 minutes to degas, and obtain the treated material;
[0028] Step 3: Pour the treated material into a mold and cure it at 160-200° C. for 3-5 hours. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0029] Beneficial effects of the present invention:
[0030] (1) The high-temperature resistant aerogel prepared by the present invention is added to the epoxy resin matrix to form a thermal insulation barrier, which limits heat transfer and can significantly improve the high-temperature resistance and thermal insulation performance of the aerogel composite material. As a result, the aerogel composite material can still have stability, reliability and low thermal conductivity in a high-temperature environment, thereby broadening the application scope of the aerogel composite material in the field of thermal insulation.
[0031] (2) The composite additive prepared by the present invention grafts caffeic acid with antioxidant effect onto the surface of vermiculite. On the one hand, after the vermiculite is grafted and modified, the compatibility between the vermiculite and the epoxy resin matrix is effectively improved, the agglomeration of the vermiculite in the matrix is avoided, and the vermiculite can be evenly distributed in the epoxy resin matrix, thereby improving the binding force between the vermiculite and the epoxy resin matrix, giving full play to the advantages of vermiculite, and improving the mechanical properties of the epoxy resin matrix. At the same time, the vermiculite has a lamellar structure and is evenly dispersed in the epoxy resin matrix. It can form a physical barrier layer, which can block the infiltration of water vapor and has a synergistic hydrophobic effect with the functional additive component. On the other hand, after caffeic acid is grafted onto the vermiculite, the small molecule caffeic acid is not easy to migrate, so that the prepared composite additive has excellent antioxidant properties. When added to the epoxy resin matrix, it has long-lasting antioxidant properties, avoiding oxidation of the aerogel composite material in a hot and humid environment, thereby extending the service life of the aerogel composite material.
[0032] (3) The functional additive component prepared by the present invention contains secondary amino groups, which can cross-link and entangle with the epoxy resin molecular chain, increase the cross-linking density, enhance the compactness of the aerogel composite material structure, reduce the molecular gap, and prevent water penetration. In addition, the functional additive component contains hydrophobic siloxane and a strongly hydrophobic tert-butyl structure, which exhibits extremely low surface energy, can make the aerogel composite material more hydrophobic, and further prevent water molecules from penetrating and invading. In addition, the silicon-oxygen bond in the siloxane of the functional additive component has a high bond energy and can cross-link with the epoxy resin matrix, which can enhance the high temperature resistance of the aerogel composite material to a certain extent and has a synergistic effect with the high temperature resistant aerogel.
[0033] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 IR spectra of activated vermiculite, modified vermiculite and composite additives in the embodiments of the present invention;
[0036] Figure 2 This is an infrared spectrum of the functional added component in the embodiment of the present invention. DETAILED DESCRIPTION
[0037] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0038] Example 1
[0039] Preparation of high temperature resistant aerogel
[0040] S1. Add 20 mL of deionized water and 40 mL of ethanol to 8 mL of ethyl orthosilicate, stir and mix well, then add hydrochloric acid to adjust the pH to 3.5. After hydrolysis for 6 h, an aerogel hydrolyzate was obtained.
[0041] S2. Add 0.6 g of mullite fiber to 10 mL of aerogel hydrolyzate and disperse it evenly. Then add dilute ammonia water to adjust the pH to 7. After 2 hours, gel is formed. The gel is placed in anhydrous ethanol at room temperature and aged for 16 hours. Finally, it is dried at 60°C to obtain high-temperature resistant aerogel.
[0042] Example 2
[0043] Preparation of composite additives
[0044] Step A: 3.5 g of vermiculite was mixed with 8% hydrochloric acid solution by mass, stirred in a 75° C. water bath for 2 h, washed until neutral, and dried at 60° C. to obtain activated vermiculite;
[0045] Step B, 3.2 g of activated vermiculite was added to a 7% sodium hydroxide solution and dispersed evenly, and then 2.8 g of 1,2-epoxyhexadecane was added. The system was placed in a water bath and the temperature was raised to 60° C. After reacting for 4 hours, it was cooled, washed, filtered, and vacuum dried to obtain modified vermiculite;
[0046] Step C: 2.8 g of modified vermiculite was added to dimethyl sulfoxide and dispersed evenly, 2.3 g of caffeic acid and 0.3 g of p-toluenesulfonic acid were added, and then the temperature was raised to 95° C., reacted for 5 h, centrifuged, washed, and vacuum dried to obtain a composite additive.
[0047] The activated vermiculite, modified vermiculite and composite additives were tested by Fourier infrared spectrometer. Figure 1 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of activated vermiculite, 3408cm -1 The absorption peak of hydroxyl group appeared at 1015cm -1 There is a Si-O absorption peak at 689 cm -1 The absorption peak of Al-O-Si appears at 2960cm -1 -2865cm -1 The absorption peaks of methylene and methyl appeared at 1030 cm -1 The absorption peak area of Si-O increases; in the infrared spectrum of the composite additive, 3069cm -1 The absorption peak of CH in the carbon-carbon double bond appears at 3026 cm -1 The absorption peak of CH in the benzene ring appears at 1730 cm -1 The absorption peak of C=O in the ester group appears at
[0048] Example 3
[0049] Preparation of functional additives
[0050] I. Add 3 g of polyisoprene to toluene, stir evenly, and introduce nitrogen protection. Then add 2.5 g of mercaptoethylamine and 0.3 g of benzoin dimethyl ether. React under ultraviolet light for 2.5 h. After the reaction is completed, wash and vacuum dry to obtain modified polyisoprene.
[0051] II. Add 2.6 g of modified polyisoprene to N,N-dimethylformamide, stir evenly, introduce nitrogen protection, then add 2 g of 3-bromopropyl tert-butyl dimethylsilyl ether and 0.4 g of triethylamine, raise the temperature to 70°C, react for 5 hours, cool to room temperature, wash, and vacuum dry to obtain a functional additive component.
[0052] The functional added components were tested by Fourier infrared spectrometer, such as Figure 2 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of the functional added components, 3414cm -1 The absorption peak of NH appears at 2960-2850cm -1 The absorption peaks of methylene and methyl appeared at 1367 cm -1 The absorption peak of tert-butyl appeared at 1176 cm -1 The absorption peak of CSC appeared at 1032 cm -1 The absorption peak of Si-OC appears at 798 cm -1 The absorption peak of Si-C appears at
[0053] Example 4
[0054] Preparation of aerogel composites
[0055] Step 1: 70 g of epoxy resin, 40 g of acetone, 1 g of anti-ultraviolet additive UV-327, 1 g of flame retardant additive dimethyl methyl phosphate, 5 g of the high-temperature resistant aerogel prepared in Example 1, 3 g of the composite additive prepared in Example 2, and 4 g of the functional additive component prepared in Example 3 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1000 r / min for 3 min to obtain a mixture;
[0056] Step 2: add 10 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 20 minutes to degas to obtain a treated material;
[0057] Step 3: Pour the treated material into a mold and cure it at 160° C. for 3 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0058] Example 5
[0059] Preparation of aerogel composites
[0060] Step 1: 80 g of epoxy resin, 50 g of acetone, 2 g of anti-ultraviolet additive UV-327, 2 g of flame retardant additive dimethyl methyl phosphate, 6 g of the high-temperature resistant aerogel prepared in Example 1, 5 g of the composite additive prepared in Example 2, and 5 g of the functional additive component prepared in Example 3 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1500 r / min for 4 min to obtain a mixture;
[0061] Step 2: add 12 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 30 minutes to degas to obtain a treated material;
[0062] Step 3: Pour the treated material into a mold and cure it at 180° C. for 4 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0063] Example 6
[0064] Preparation of aerogel composites
[0065] Step 1: 90 g of epoxy resin, 60 g of acetone, 3 g of anti-ultraviolet additive UV-327, 3 g of flame retardant additive dimethyl methyl phosphate, 8 g of the high-temperature resistant aerogel prepared in Example 1, 6 g of the composite additive prepared in Example 2, and 6 g of the functional additive component prepared in Example 3 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 2000 r / min for 5 min to obtain a mixture;
[0066] Step 2: add 15g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 40 minutes to degas to obtain a treated material;
[0067] Step 3: Pour the treated material into a mold and cure it at 200° C. for 5 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0068] Comparative Example 1
[0069] Preparation of aerogel composites
[0070] Step 1: 80 g of epoxy resin, 50 g of acetone, 2 g of anti-ultraviolet additive UV-327, 2 g of flame retardant additive dimethyl methyl phosphate, 5 g of the composite additive prepared in Example 2, and 5 g of the functional additive component prepared in Example 3 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1500 r / min for 4 min to obtain a mixture;
[0071] Step 2: add 12 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 30 minutes to degas to obtain a treated material;
[0072] Step 3: Pour the treated material into a mold and cure it at 180° C. for 4 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0073] Comparative Example 2
[0074] Preparation of aerogel composites
[0075] Step 1: 80 g of epoxy resin, 50 g of acetone, 2 g of anti-ultraviolet additive UV-327, 2 g of flame retardant additive dimethyl methyl phosphate, 6 g of the high-temperature resistant aerogel prepared in Example 1, and 5 g of the functional additive component prepared in Example 3 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1500 r / min for 4 min to obtain a mixture;
[0076] Step 2: add 12 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 30 minutes to degas to obtain a treated material;
[0077] Step 3: Pour the treated material into a mold and cure it at 180° C. for 4 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0078] Comparative Example 3
[0079] Preparation of aerogel composites
[0080] Step 1: 80 g of epoxy resin, 50 g of acetone, 2 g of anti-ultraviolet additive UV-327, 2 g of flame retardant additive dimethyl methyl phosphate, 6 g of the high-temperature resistant aerogel prepared in Example 1, and 5 g of the composite additive prepared in Example 2 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1500 r / min for 4 min to obtain a mixture;
[0081] Step 2: add 12 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 30 minutes to degas to obtain a treated material;
[0082] Step 3: Pour the treated material into a mold and cure it at 180° C. for 4 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0083] Comparative Example 4
[0084] Preparation of aerogel composites
[0085] Step 1: 80 g of epoxy resin, 50 g of acetone, 2 g of anti-ultraviolet additive UV-327, 2 g of flame retardant additive dimethyl methyl phosphate, 6 g of the high-temperature resistant aerogel prepared in Example 1, 5 g of vermiculite, and 5 g of the functional additive component prepared in Example 3 were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1500 r / min for 4 min to obtain a mixture;
[0086] Step 2: add 12 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 30 minutes to degas to obtain a treated material;
[0087] Step 3: Pour the treated material into a mold and cure it at 180° C. for 4 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0088] Comparative Example 5
[0089] Preparation of aerogel composites
[0090] Step 1: 80 g of epoxy resin, 50 g of acetone, 2 g of anti-ultraviolet additive UV-327, 2 g of flame retardant additive dimethyl methyl phosphate, 6 g of the high-temperature resistant aerogel prepared in Example 1, 5 g of the composite additive prepared in Example 2, and 5 g of polyisoprene were added to a mixing tank and mixed evenly. The mixture was centrifuged at 1500 r / min for 4 min to obtain a mixture;
[0091] Step 2: add 12 g of methyltetrahydrophthalic anhydride to the mixture, stir evenly, and place in a vacuum drying oven for 30 minutes to degas to obtain a treated material;
[0092] Step 3: Pour the treated material into a mold and cure it at 180° C. for 4 h. After curing, cool it naturally and demould it to obtain an aerogel composite material.
[0093] Performance testing
[0094] The properties of the aerogel composite materials prepared in Example 4 to Example 6 and Comparative Example 1 to Comparative Example 5 were tested. 5 mg of the aerogel composite material was weighed and placed in an oven. The temperature was raised from 25°C to 800°C at a heating rate of 10°C / min. The initial decomposition temperature of the aerogel composite material was recorded to determine the high temperature resistance of the aerogel composite material. According to the GB / T10295-2008 standard, the thermal conductivity of the aerogel composite material was tested to determine the thermal insulation performance of the aerogel composite material. According to the GB / T 10299-2011 standard, the hydrophobicity of the aerogel composite material was tested to determine the hydrophobic performance. According to GB / T 1040.2-2022, the tensile properties of the aerogel composite material were tested. The aerogel composite material was then placed in an aging box at 250°C. After aging for 24 hours, the tensile properties of the aerogel composite material were tested again to determine the antioxidant properties and mechanical properties of the aerogel composite material. The test results are shown in the following table:
[0095]
[0096] As can be seen from the above table, the aerogel composite materials prepared by Examples 4 to 6 of the present invention have excellent high temperature resistance, thermal insulation performance, hydrophobicity, oxidation resistance and mechanical properties, among which the test result of Example 5 is the best. Comparative Example 1 does not add high temperature resistant aerogel, and the high temperature resistance test and thermal insulation test results are poor; Comparative Example 2 does not add composite additives, and cannot utilize vermiculite to graft antioxidant small molecule caffeic acid to improve the oxidation resistance, hydrophobicity and mechanical properties of the aerogel composite material, so the oxidation resistance test, hydrophobicity test and mechanical property test results are poor; Comparative Example 3 does not add functional additives, and cannot utilize hydrophobic siloxane and strong hydrophobic tert-butyl structure to improve the hydrophobicity of the aerogel composite material. The functional added components are cross-linked with the epoxy resin matrix to improve the density of the aerogel composite material, and the high bond energy silicon-oxygen bonds improve the high temperature resistance, so the high temperature resistance test and the hydrophobicity test results are poor; in Comparative Example 4, vermiculite is added, and the vermiculite is directly added to the epoxy resin matrix without modification, which easily causes agglomeration, so the hydrophobicity test and the mechanical property test results are poor, and it is not grafted with caffeic acid with an antioxidant effect, so the antioxidant performance test result is poor; in Comparative Example 5, polyisoprene is added, and the hydrophobicity cannot be improved by utilizing the tert-butyl structure and siloxane with strong hydrophobicity, and the high bond energy silicon-oxygen bonds and cross-linking with the epoxy resin matrix are generated, so the high temperature resistance test and the hydrophobicity test results are poor.
[0097] The above content is merely an example and explanation of the concept of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. A high temperature hydrophobic aerogel composite material, characterized in that: The raw materials include the following parts by weight: 70-90 parts of epoxy resin, 40-60 parts of diluent, 10-15 parts of curing agent, 1-3 parts of anti-ultraviolet additive, 1-3 parts of flame retardant additive, 5-8 parts of high temperature resistant aerogel, 3-6 parts of composite additive, and 4-6 parts of functional additive components; The preparation method of the composite additive comprises the following steps: Step A, adding activated vermiculite to a sodium hydroxide solution with a mass fraction of 6-8% and dispersing the mixture evenly, adding an epoxy modifier, and then placing the mixture in a water bath and raising the temperature to 60-70° C., reacting for 3-5 hours, cooling, washing, filtering, and vacuum drying to obtain modified vermiculite; Step B, adding modified vermiculite to dimethyl sulfoxide and dispersing it evenly, then adding caffeic acid and p-toluenesulfonic acid, and then raising the temperature to 85-95° C., reacting for 4-6 hours, centrifuging, washing, and vacuum drying to obtain a composite additive; The preparation method of the functional additive component comprises the following steps: Ⅰ. Add polyisoprene to toluene, stir evenly, introduce nitrogen protection, then add mercaptoethylamine and benzoin dimethyl ether, and react under ultraviolet light for 2-3 hours. After the reaction is completed, wash and vacuum dry to obtain modified polyisoprene; Ⅱ. Add modified polyisoprene to N,N-dimethylformamide, stir evenly, introduce nitrogen protection, then add 3-bromopropyl tert-butyl dimethylsilyl ether and alkaline catalyst, raise the temperature to 60-80°C, react for 4-6h, cool to room temperature, wash, and vacuum dry to obtain functional additive components.
2. A high temperature hydrophobic aerogel composite material according to claim 1, characterized in that: The method for preparing the high temperature resistant aerogel comprises the following steps: S1. Add deionized water and ethanol to tetraethyl orthosilicate, stir and mix evenly, add hydrochloric acid to adjust the pH to 3-4, and hydrolyze for 4-6 hours to obtain an aerogel hydrolyzate; S2. Add mullite fiber to the aerogel hydrolyzate and disperse it evenly, then add dilute ammonia water to adjust the pH to 6-8. After 1-2 hours, gel is formed. The gel is placed in anhydrous ethanol at room temperature for aging for 12-18 hours, and finally dried at 45-65°C to obtain high temperature resistant aerogel.
3. A high temperature hydrophobic aerogel composite material according to claim 2, characterized in that: In step S2, the mass percentage of the mullite fiber in the aerogel hydrolyzate is 6-8%.
4. The high temperature hydrophobic aerogel composite material according to claim 1, characterized in that: In step A, the method for activating vermiculite is to mix the vermiculite with a hydrochloric acid solution with a mass fraction of 6-8%, stir for 1-2 hours in a water bath at 70-80° C., wash to neutrality, and dry at 50-60° C. to obtain activated vermiculite.
5. The high temperature hydrophobic aerogel composite material according to claim 1, characterized in that: In step A, the epoxy modifier is any one of 1,2-epoxydodecane, 1,2-epoxytetradecane, 1,2-epoxyhexadecane or 1,2-epoxyoctadecane.
6. The high temperature hydrophobic aerogel composite material according to claim 1, characterized in that: In step II, the basic catalyst is triethylamine or pyridine.
7. The high temperature hydrophobic aerogel composite material according to claim 1, characterized in that: The diluent is acetone or xylene; the curing agent is methyltetrahydrophthalic anhydride or methylhexahydrophthalic anhydride; the anti-ultraviolet additive is UV-1577 or UV-327; and the flame retardant additive is dimethyl methyl phosphate or toluene diphenyl phosphate.
8. A method for preparing a high temperature hydrophobic aerogel composite material as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add epoxy resin, diluent, anti-ultraviolet additive, flame retardant additive, high temperature resistant aerogel, composite additive and functional additive component into a mixing tank and mix them evenly. Centrifuge the mixture at 1000-2000 r / min for 3-5 minutes to obtain a mixture. Step 2: Add the curing agent to the mixture, stir evenly, place in a vacuum drying oven and evacuate for 20-40 minutes to degas, and obtain a treated material; Step 3: pour the treated material into a mold, cure it at 160-200° C. for 3-5 hours, and after curing, naturally cool and demould to obtain an aerogel composite material.
Citation Information
Patent Citations
A method for preparing a low thermal conductivity aerogel-type epoxy resin thermal insulation composite material
CN113512272B
Composite insulation board containing hybrid aerogel and preparation method thereof
CN118290904A